Possibilities of using sulphur and plant origin waste for light-weight and thermal insulation construction composites - Marčiukaitis, Gediminas; Jurkėnas, Gintaras (Journal of Environmental Engineering and Landscape Management, 2013)
The article notes that not all types of plant origin waste are appropriate for being used as fuel or left for decay. The environment is polluted by noxious gas that is generated in the process of heating or decaying. Sulphur waste is produced at chemical and oil industry plants as well as during the treatment of emissions resulting from fuel combustion. Thermal energy is produced in the process of combusting plant origin waste; however, the emitted fumes are pollutants. A much more effective way for the use of this waste is proposed, i.e. to produce and use a new type of thermal insulation construction composites that would allow long-term heat saving buildings. The performed tests covered the properties of components and the influence of plasticisers on the plasticity and compressive strength of hardened sulphur. The common behaviour of sulphur and plant origin waste – sawdust, boon, straw – in composite was also analysed. All the properties necessary for thermal insulation materials were identified – compressibility, compression and bending strength, thermal conductivity. They have the same value as other classical thermal insulation materials.